Pengaruh Keragaman Produk Dan Harga Terhadap Keputusan Pembelian Konsumen Di Toko Sepeda Purgiono Kota Nganjuk - Maxsrita Tassya Sari; Bambang Suwarsono; Brahma Wahyu Kurniawan (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
Very tight competition in the business world means entrepreneurs have to think about what consumers want, including looking at product diversity and prices. The aim of the research is to explain the influence of product diversity and prices partially and simultaneously on purchasing decisions at the Purgiono Bike Shop, Nganjuk City. This research uses quantitative methods. The population taken was 1,680 consumers using Non Probability techniques. The sample obtained was 94 respondents using the Slovin formula. Data processing uses the SPSS program. The results of this research are that product diversity and price have a significant simultaneous influence on purchasing decisions at the Purgiono Bike Shop, Nganjuk City.